(untitled) - Miller, Joseph B. (Westport, Conn., 2009)
Why another book about the Internet? The answer is simple: while there are a number of excellent books on various aspects of networking, the Internet, HTML, Web design, Web programming, XML, and Web searching, there is not a single survey text that explores each of these topics holistically in the context of the knowledge and skill needs of those preparing for careers in any of the many information technology (IT) intensive fields such as library and information science (LIS), business and management information systems (MIS), and decision science (DIS), to name but a few. Part I focuses on the technologies of the Internet. Part 2 focuses on the many forms of Internet content and how it is created. Part 3 is devoted to the topic of Internet information retrieval
Keywords: Thư viện,Libraries; Công nghệ thông tin